EFISIENSI PEMASARAN BERAS DI KABUPATEN CIAMIS DAN JAWABARAT - Eti Suminartika; Iin Djuanalia (Universitas Galuh Ciamis, 2017)
Rice is the staple food for Indonesian people, to maintain domestic supply, rice market must be efficient. The purposes of this study are to analyze: (1) Marketing cost and (2) Marketing efficiency. This study used survey methods, snowball sampling is done in this study, data used consist of primary and secondary data, the data were analyzed by mathematic and descriptive analyze, the location of the study is in the centre of rice production in Ciamis district and centre of rice production in West Java. The results show that thr rice marketing in Ciamis is more efficient than those of West Java Province, this condition is due to low cost of marketing and lower price of paddy, therefore the rice which produced in Ciamis district has competitve advantage in the market in West Java.